Book review: Tenterfield: My happy childhood in care, by Margaret Irvine Edinburgh, Fledgling Press, 2010, 226 pp, ISBN 978-1-905916-26-9 - Irene Stevens (Scottish Journal of Residential Child Care)
When I first saw this book, I was slightly taken aback by the tide. This personal reaction caused me co reflect a little on how residential care is represented in the wider world. I reached the conclusion chat both the media and certain policy documents paint such a poor picture of residential care that we become shocked if anyone says a good word about our profession. Yet in my own experience, I know chat a huge amount of excellent work happens. I would say chat the majority of young people with whom my colleagues have worked would admit co being better off for having experienced true caring relationships from residential child care practitioners. This book is an affirmation of my personal experience and that of my colleagues.